Pengaruh Insentif Dan Jaminan Sosial Terhadap Produktivitas Kerja Karyawan Pada PT. Astra Daihatsu Malalayang Manado - Ribka Natasia Rori; Cherys Laloan; Iwan Kandori (Literacy: Jurnal Pendidikan Ekonomi, 2020)
The purpose of this study was to determine the effect of incentives and social security on employee productivity at PT. Astra Daihatsu Malalayang Manado. This research method is a survey method with a sample of 33 from a total population of 36. Based on the results of the study, there is a significant influence between the Incentive variable on Work Productivity, so if employee work productivity goes well, the incentive can increase. So if employee work productivity goes well, incentives can increase. There is a significant influence between the Social Security variable on Work Productivity, so if employee work productivity goes well, Social Security will be provided by the company. There is a significant influence between the Incentive variable and the Social Security variable together on Work Productivity, the Incentive variable and the Social Security variable have an effect or have a joint relationship with the Work Productivity variable.